Prognostic factors for the severe course of COVID-19 in the different COVID-19 peak periods in Central Kazakhstan - Lyudmila Turgunova; Irina Mekhantseva; Irina Bacheva; Dana Amirkhanova; Maria Butyugina; Nadezhda Samoilova (National Scientific Medical Center, 2022)
Introduction: COVID-19 has become the cause of a pandemic that has swept the entire world. Considering the genetic variability of the virus, the development and implementation of antiviral therapies, and the acquisition of a society's immune defenses through past infection or vaccination, the course of COVID-19 may change over time. The research aim was to study the prognostic significance of clinical and laboratory parameters with severe COVID-19 in 2020 and 2021 in Central Kazakhstan.  Material and methods: A cohort of 1556 patients with COVID-19 admitted to the infection hospitals of Karaganda from May to July 2020 and 2021 year was retrospectively analyzed. The association of clinical and laboratory parameters with the severe disease was analyzed using univariate and multivariate logistic regression, and independent predictors were established for each factor.  Results: The comparative analysis of the prognostic significance of demographic, clinical, and laboratory parameters in different periods of the pandemic showed a reduction in developing severe COVID-19 among hospitalized patients in 2021 compared to 2020. The essential value of comorbidity, especially chronic renal failure, and chronic heart failure remained significant against the background of decreasing prognostic significance of age, gender, and clinical and laboratory indicators of inflammation for the severe course of COVID-19.